Pendidikan Al-Ghazali Dan Implementasinya Dalam Pendidikan di Indonesia - Ummah, Anjani Rohmatul; Khuriyyah, Nurul; Salsabila, Nur Aliyah; Abu Bakar , M. Yunus (SM Institute, 2025)
Al-Ghazali's view on the purpose and method of Islamic education. According to Al-Ghazali, Islamic education aims to form a complete person who strives to achieve perfection in this world and the hereafter. Humans are considered to achieve perfection if they seek knowledge and practice the virtues (fadhilah) obtained from knowledge. The main goal of education in Islam is taqarrub (self-approach) to Allah, where the most perfect human being is the one who always gets closer to the Creator. Al-Ghazali differentiated educational methods into two categories: first, special methods of religious education, which focus on the formation of aqidah and morality of learners; and second, special methods of moral education, where teachers must be sensitive to individual differences and use approaches that suit the needs of each student. Education according to Al-Ghazali has a strong religious and moral orientation, without neglecting worldly needs. This article highlights the relevance of Al-Ghazali's views in the context of modern education, especially in emphasizing the balance between intellectual, spiritual, and moral aspects. Keywords : Al-Ghazali; Islamic education; taqarrub; morals; educational methods.